2013
DOI: 10.9775/kvfd.2012.7754
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic, Genotypic Characterisation and Antimicrobial Susceptibility Determination of Lactococcus garvieae Strains

Abstract: SummaryIn this study, phenotypic and genotypic features of 10 L. garvieae strains isolated from rainbow trout farms were examined with 3 reference strains (Spain, England and ATCC 43921) comperativly. Rapid 32 STREP and conventional microbiologic tests were used for determining phenotipic features of L. garvieae strains. Altough there are diff erences, in Rapid 32 STREP system, between strains in terms of β-Glucuronidase, D-ribose, sorbitol, lactose, raffinose, alanyl-phenylalanyl-proline arylamidase, pyrrolid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 10 publications
2
25
0
Order By: Relevance
“…Lactococcosis outbreaks have been regularly observed in rainbow trout since 2001 in Turkey (Avcı, Aydogan, Tanrıkul, & Birincioğlu, ; Diler, Altun, Adıloglu, Kubilay, & Isıklı, ; Tanrikul & Gultepe, ). Therefore, L. garvieae is now considered as one of the most important pathogens in the rainbow trout industry in Turkey (Altun, Onuk, Ciftci, Buyukekiz, & Duman, ). Lactococcosis outbreaks in aquaculture are treated with antibiotics, but these are often ineffective, and their indiscriminate use has led to an increase in antibiotic resistance (Pérez‐Sánchez, Balcázar, Garcia, et al., ; Romalde & Toranzo, ; Vendrell et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Lactococcosis outbreaks have been regularly observed in rainbow trout since 2001 in Turkey (Avcı, Aydogan, Tanrıkul, & Birincioğlu, ; Diler, Altun, Adıloglu, Kubilay, & Isıklı, ; Tanrikul & Gultepe, ). Therefore, L. garvieae is now considered as one of the most important pathogens in the rainbow trout industry in Turkey (Altun, Onuk, Ciftci, Buyukekiz, & Duman, ). Lactococcosis outbreaks in aquaculture are treated with antibiotics, but these are often ineffective, and their indiscriminate use has led to an increase in antibiotic resistance (Pérez‐Sánchez, Balcázar, Garcia, et al., ; Romalde & Toranzo, ; Vendrell et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…; Altun et al . ). Rainbow trout is the most commonly aquacultured inland water fish in Turkey (TÜİK ).…”
Section: Discussionmentioning
confidence: 97%
“…AACGCCGCGTGAGTGAAGAAGGTTTTCGGATCGTAAAACTCTGTTGTTAG ************************************************** Previous studies have revealed that L. garvieae strains may have variations in utilisation of hippurate, β-glucuronidase, citrate, Voges-Proskauer (VP), pyrrolidonyl arylamidase, urease, and also in acid production from D-mannose, D-lactose, D-ribose, sorbitol and raffinose (Çağırgan, 2004;Soltani, Nikbakht, Ebrahimzadeh Moussavi, & Ahmadzadeh, 2008;Altun et al, 2013;Didinen, Yardimci, Onuk, Metin, & Yildirim, 2014). Similarly, it has been observed in the present study that isolates were found to have different phenotypic profiles in acid production from ribose and lactose (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…This research also indicated isolates previously recorded as resistant to sulphamethoxazole/trimethoprim and susceptible to erythromycin (Diler et al, 2002;Kav & Erganiş, 2007;Raissy & Ansari, 2011;Didinen et al, 2014), to be of intermediate profile. To prevent the emergence of antibiotic resistance and the failure in disease treatment, it should be determined of antibiotic susceptibility profiles of bacteria and applied of suitable antimicrobial agents in sufficient dosage and time (Altun et al, 2013). Pathogenic bacteria which acquire antibiotic resistance continue to survive and maintain the capacity to cause disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation